Nuclear Deformation Shape of Even- Even 122-146Ba and 200-214Pb Isotopes - Ayad.E. Ezwam (The Libyan Journal of Science, 2024)
In this paper, the shape for even-even 122146 Ba and 200214 Pb nuclei have been studied, by using deformed shell model equations, to calculate the reduced electric transition probability B (E 2)  ,between the ground state and first excited state to calculate nucleus quadrupole deformation parameter  for understanding the shape of nuclei as well as the intrinsic quadrupole moment Q0andtherootmeansquareoftheradius r2 12werecalculated,andhavebeen used through calculating major ( a ) and minor ( b )ellipsoid axes and the different between them R . The relationship between the difference of the major and minor elliptical axes (a,b) and neutrons number was studied. It’s clear that the R and the deformation parameters  of 56 Ba and 82 Pb isotopesdecreasedwhentheneutronsnumberreachtothemagicnumber N 82 and N  126 . To achieve our mean purposes which determine the identify if the nucleus under the study has prolate, oblate or spherical shape, we have been compared our calculations with the stander values for the experimental Rexp range. Finally, the nucleus under the study was plotted in two dimensions 2D depending on the value of (a,b ) .